EFEKTIVITAS STRATEGI PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN HASIL BELAJAR IPS DI SEKOLAH DASAR - Lubis, Yusma Fadhilah; Amy Khaliza Sirait; Gustyven Tambunan; Amelia Lestari Sinambela; Nefo Puspita Lubis; Khairunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a literature review aimed at examining the effectiveness of cooperative learning strategies in improving learning outcomes in Social Studies (IPS) subjects at the elementary school level. Cooperative learning strategies have been widely adopted as a teaching method that encourages active student participation, enhances learning motivation, and strengthens conceptual understanding collaboratively. Through analysis of various related studies and scientific articles, it was found that the implementation of cooperative learning has a significant positive impact on the achievement of Social Studies learning outcomes, both cognitively and socially. Additionally, this strategy helps develop students’ communication and teamwork skills. The findings of this review are expected to serve as a reference for educators and researchers in developing effective teaching models in elementary schools, particularly for Social Studies subjects.